Default Mode Network as a Neural Substrate of Acupuncture: Evidence, Challenges and Strategy - Zhang, Yuqi; Zhang, Haolin; Nierhaus, Till; Pach, Daniel; Witt, Claudia M.; Yi, Ming (Frontiers in Neuroscience, 2019)
Acupuncture is widely applied all over the world. Although the neurobiological underpinnings of acupuncture still remain unclear, accumulating evidence indicates significant alteration of brain activities in response to acupuncture. In particular, activities of brain regions in the default mode network (DMN) are modulated by acupuncture. DMN is crucial for maintaining physiological homeostasis and its functional architecture becomes disrupted in various disorders. But how acupuncture modulates brain functions and whether such modulation constitutes core mechanisms of acupuncture treatment are far from clear. This Perspective integrates recent literature on interactions between acupuncture and functional networks including the DMN, and proposes a back-translational research strategy to elucidate brain mechanisms of acupuncture treatment.